Islamic Central Asia : an anthology of historical sources - Levi, Scott Cameron; Sela, Ron (Indiana University Press, 2010)
The first English-language anthology of primary documents for the study of Central Asian history. Scott C. Levi and Ron Sela draw from a vast array of historical sources to illustrate important aspects of the social, cultural, political, and economic history of Islamic Central Asia, from the 7th-century Arab conquests to the 19th-century Russian colonial era. --from publisher description.